Underwear Passing Ability In Volleyball Games In Grade V Students of SD Negeri Mawas - Latuheru, Ricardo Valentino (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study investigates the effectiveness of a structured underhand passing training program on the volleyball skills of Grade V students at Mawas State Elementary School. Utilizing a quasi-experimental design, 60 students were randomly divided into two groups: an experimental group (n = 30) that received specialized underhand passing training, and a control group (n = 30) that followed the standard physical education curriculum. Pretest and posttest evaluations were conducted using the Brumbach Forearm Pass Test. The pretest results showed similar baseline performance between groups, with mean scores of 55.23 for the experimental group and 54.87 for the control group. After six weeks of intervention, the experimental group showed a significant improvement to 68.47, while the control group improved slightly to 58.10. A paired sample t-test revealed a statistically significant difference in the experimental group (p < 0.05), while the control group's improvement was not significant (p = 0.068). An independent sample t-test confirmed a significant difference between the two groups in the post-test (p < 0.05). Qualitative data supported the quantitative findings, with students in the experimental group exhibiting higher enthusiasm, better discipline, and improved motor coordination. These results highlight the value of structured, age-appropriate training programs in enhancing basic volleyball skills in elementary school settings. The study suggests incorporating targeted skill development modules into physical education curricula to promote both performance and engagement.